Implementation of Supervision and Evaluation by the Directorate of Shipping and Marine Affairs to the Siuppak Owner Company - Fatimah, Fatimah; Herjuna, Hadhitya (RSF Conference Series: Engineering and Technology, 2023)
The Ministry of Shipping and Marine Affairs (DITKAPEL) is part of the Directorate General of Sea Transportation of the Ministry of Transportation, which manages the distribution of Indonesian ships and crews. The large number of Indonesian Workers (TKI) who work as Crew Officers (ABK) is the object of violations and problems, especially from the company. To do so, the government must increase supervision and protection for them by monitoring the company that owns SIUPPAK. SIUPPAK is the permit for the company to recruit and place the crew on board. For this reason, the objective of the study is to find out the forms of violations committed by the SIUPPAK owner company and the sanctions given to companies holding SIUPPAK for abuse of authority committed.. The research method used in this study is a descriptive qualitative method by describing completely and systematically the supervision and evaluation carried out by DITKAPEL on companies that own SIUPPAK. The data sources used are primary and secondary data sources obtained through interviews, observations, documentation, and literature studies. The results showed that there were a number of companies that owned SIUPPAK that committed violations. These companies received sanctions in the form of Warning Letter 1, Warning Letter 2, Warning Letter 3, and Company Inactivity. Supervision and evaluation by DITKAPEL on the company that owns SIUPPAK is carried out periodically, called the Annual Audit. The annual audit carried out is in accordance with the established standards, and the DITKAPEL follows up on cases of violations wisely and firmly in accordance with existing regulations.